Effect of Dilute Acid - Alkaline Pretreatment on Rice Husk Composition and Hydrodynamic Modeling with CFD - Novia Novia; Vishnu K Pareek; Hermansyah Hermansyah; Asyeni Miftahul Jannah (Science and Technology Indonesia, 2019)
The high cellulosic content of rice husk can be utilized as a feedstock for pulp and biofuel. Pretreatment is necessary to break the bonds in the complex lignocellulose matrices addressing the cellulose access. This work aims to utilize the rice husk using dilute acid and alkaline pretreatment experimentally and CFD modeling. The study consists of three series of research. The first stage was the dilute acid pretreatment with sulfuric acid concentration of 1% to 5% (v/v) at 85°C for 60 minutes, and alkaline pretreatment with NaOH concentration of 1% to 5% (w/v) at 85oC for 30 minutes separately. The second stage used the combination of both pretreatment. Moreover the last stage of research was hydrodynamic modeling of pretreatment process by CFD (ANSYS FLUENT 16). The experimental results showed that the lowest lignin content after acid pretreatment was about 10.74%. Alkaline pretreatment produced the lowest lignin content of 4.35%. The highest cellulose content was 66.75 % for acid-alkaline pretreatment. The lowest content of lignin was about 6.09% for acid-alkaline pretreatment. The lowest performance of alkaline pretreatment on HWS (hot water solubility) of about 7.34% can be enhanced to 9.71% by using a combination alkaline-acid. The combined pretreatments result hemicellulose of about 9.59% (alkaline-acid) and 9.27% (acid-alkaline). Modeling results showed that the mixing area had the minimum pressure of about -6250 Pa which is vortex leading minimum efficiency of mixing. The rice husk flowed upward to the upper level and mixed with reagent in the perfect mixing.